Impacts on the mental health of nursing professionals involved in the front line in the fight against COVID-19: an integrative review (Research, Society and Development, 2022)
Objective: to investigate the impacts on the mental health of nursing professionals directly involved in the fight against COVID-19. Methodology: an integrative review was carried out. Searches were carried out for materials published in databases from November 2019 to September 2021, using the descriptors "pandemic", "COVID-19", "nursing", "health professionals" and "mental health". Results: in the factors that impacted the mental health of the nursing professional, the precarious working conditions, lack of materials, PPE, technical skills and rest, long working hours were highlighted; impact the mental health of the professional, with feelings such as anxiety, fear, insomnia, stress, depression and Burnout Syndrome; in terms of mental health promotion actions, the use of technologies to contact family and friends, the use of integrative and complementary practices such as auriculoacupuncture, expansion of the supervision of working conditions by the Federal Nursing Council, were highlighted. check PPE availability and workflow. Conclusion: nurses have been facing impacts on their mental health, due to the lack of working conditions, lack of PPE, training and work overload, requiring training, protection and safety actions, as well as psychological support and public policies aimed at mental health of these workers.